1996
DOI: 10.1161/01.atv.16.8.1007
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Production by Macrophages From Atheromatous Plaques

Abstract: Interleukin-8 (IL-8) is a chemotactic peptide produced by macrophages that may be involved in the recruitment of inflammatory cells into atherosclerotic plaques. In vitro, IL-8 production by macrophages isolated from carotid plaques (1240 +/- 510 pg.10(5) cells-1.24h-1, mean +/- SEM, n = 6) and noncarotid plaques (4312 +/- 1588 pg.10(5) cells-1.24 h-1, n = 9) was significantly greater than IL-8 production by blood monocytes isolated from the same patients (526 +/- 278 pg.10(5) cells-1.24 h-1, n = 6, P < .05 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 21 publications
2
85
0
6
Order By: Relevance
“…Human atheroma contain various chemokines including MCP-1, IL-8, MIP-1␤, IP-10, and RANTES (23)(24)(25)(26). Targeted disruption of the gene for MCP-1, its receptor CCR-2, or the murine homologue of IL-8 receptor, CXCR-2, significantly decreased atherogenesis in mice (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Human atheroma contain various chemokines including MCP-1, IL-8, MIP-1␤, IP-10, and RANTES (23)(24)(25)(26). Targeted disruption of the gene for MCP-1, its receptor CCR-2, or the murine homologue of IL-8 receptor, CXCR-2, significantly decreased atherogenesis in mice (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MCP-1 is synthesized in inflamed gingiva by vascular endothelial cells and mononuclear phagocytes [12]. Apostolopoulos et al [13] found IL-8 mRNA in carotid plaque, and Moreau et al [14] showed that IL-8 played a potential role in atherogenesis by inhibiting tissue inhibitors of metalloproteinase-1 expression. MCP-1 has been suggested to induce macrophage infiltration into the arterial wall [15].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Furthermore, peripheral blood mononuclear cells from hypercholesterolemic patients have a marked enhancement of IL-8 production. 31 Mice do not express a peptide homologue of IL-8, but they do express one of the GRO chemokines, KC/GRO-␣, in the intima of advanced atherosclerotic lesions in the chimeric LDLR Ϫ/Ϫ mice.…”
mentioning
confidence: 99%